Professional Liability Insurance Contracts: Claims Made Versus Occurrence Policies - Boyer, Martin; Gobert, Karine (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l'administration, Université Laval, 2011)
We present in this paper a theoretical approach that argues when one should opt for claims-made or for occurrence-based policies in liability insurance. Occurrence-based contracts cover the policyholder for losses incurred in a given year, no matter when the claims is actually reported in the future. In claims-made contracts, losses are covered in the year in which they are reported no matter when they occured in the past provided a claims-made insurance policy was valid then. The major difference between the two types of contract is thus that occurrence contracts are forward looking whereas claims-made contracts are retrospective. The goal of this paper is to analyze in what circumstances policyholders would prefer one contract of the other.